PERANAN KOMPONEN EKSTRAKTIF KAYU DALAM MENGURANGI PEMANASAN GLOBAL - Sushardi (Jurnal Wana Tropika, 2019)
Global warming is happened cause by prolonged drought, forest fires, floods and landslides. High carbon emissions from industries, burning of forests and peatlands exacerbate these conditions. Excessive gas emission has the potential to be a barrier to the reflection of infrared rays from the earth into the atmosphere and it has a warming effect, which is then called the greenhouse effect. Wood is one of the plants that have extractive components that can absorb carbon emissions most effectively. The study aims to determine the extractive components of sengon and johar wood that can capture formaldehyde emissions. The research design used a one-factor Complete Randomized Design, namely the type of sengon wood and johar wood with analyzed using the SPSS program. The parameters observed were specific gravity, extractive content and formaldehyde emission. The results showed that sengon and johar wood types had different specific gravity, extractive content and formaldehyde emission. The average density of sengon wood is 0,236, extractive which is soluble in cold water 3,653%, in hot water 4,158%, soluble alcohol bensen 3,660%, and formaldehyde emission 0,927 ppm. The average density of johar wood is 0.650, extractive which is soluble in cold water 5.020%, in hot water 8.740%, soluble alcohol bensen 10.310% and formaldehyde emission 0.473 ppm. Extractive components that play an important role in absorbing carbon emissions are extractive components that dissolve in cold water and hot water, where the extractive component contains polar organic compounds, such as sugar, dyes, tannin, gum, protein and starch. Keywords: Extractive, global warming, formaldehyde emissions